“At Lost for Words”: A Case Study on the Dialect Vocabulary Knowledge among Bruneian Youths in a Higher Institute of Education - Norazmie Yusof; Balazs Huszka; Yabit Alas; Harun Joko Prayitno; Minah Sintian (Talenta Publisher, 2023)
This study aimed to identify the knowledge of Brunei Malay dialect vocabulary among youths and to discuss the challenges as well as steps in enhancing the knowledge of this dialect. Brunei Malay dialect or known as ‘Cakap Barunai’ is a dialect widely used among Bruneians, and considered as the mother tongue and the daily communication language among the locals. According to studies, the Ethno Vitality Rate of Brunei Malay dialect was high and considered safe; however, recent trends have shown decreasing usage of Brunei Malay especially among the Bruneian youths (15-40 years old). There are insufficient studies to ascertain whether this trend affects the youths’ Brunei Malay vocabulary knowledge. This study adapted the Vocabulary Knowledge Scale (VKS) test on the Brunei Malay vocabulary and a set of survey containing Likert scale and open-ended questions to collect the research data distributed among 102 respondents. Based on the data, the knowledge of Brunei Malay dialect was considered low as only 20.9% received responses that indicated the correct vocabulary’s meaning. The survey showed that influences from different languages and social media, and lack of exposure and intergenerational transfer were the main causes of this issue. Suggestions to preserve this dialect included education, campaigns, social media and family involvement.